Differences between dedicated and not dedicated hospice physicians in symptoms and signs improvement among advanced cancer patients. Issue 32 (13th August 2021) - Chung, Jae Ho; Kim, Sun Hyun; Suh, Sang-Yeon; Cheng, Shao-Yi; Mori, Masanori; Yamaguchi, Takashi; Chen, Ping-Jen; Morita, Tatsuya; Tsuneto, Satoru
Abstract : Abstract: The hospice and palliative care can improve the symptoms and signs of terminal cancer patients. The purposes of this study are how to improve terminally ill cancer patients' symptoms and signs and how the dedicated palliative care service effects on these improvements. From January 2017 to March 2019, among 919 terminally ill cancer patients admitted to the palliative care units in 11 hospitals of South Korea, we analyzed 334 patients with prospective cohort method and categorized them into non-dedicated hospice care group of 234 and dedicated hospice care group of 100. Symptoms improvement of dyspnea, fatigue, drowsiness, and dry mouth during the first week of admission were respectively 298 (89.2%), 25 (7.5%), 204 (61.1%), 76 (22.8%). Signs improvement of myoclonus, respiratory secretion, leg edema, and ascites between admission and a week after were 5 (1.5%), 41 (12.3%), 47 (14.1%), 12 (3.6%). Significant differences between dedicated hospice care physician group and non-dedicated hospice care physician group were shown in drowsiness (67.5% vs 46%, P  < .001) and respiratory secretion (15% vs 6%, P  < .028). Compared to non-dedicated care group, the odds ratio for more than 2 symptoms or signs was 1.78 (95% confidence interval, 1.05–3.02) in the dedicated care group after adjusting confounding variables. In conclusion, terminally ill cancer patients who received palliative or hospice service showed significant improvement in symptoms and signs. And, family doctors (dedicated hospice physician group) performed better than oncologists (non-dedicated physician group).